Piezoelectric intrinsic polarity modeling and determination - Yuriy Poplavko (APL Materials)
The intrinsic electric polarity of piezoelectrics determines their non-centrosymmetric structure and significantly affects not only their electrical properties but also their mechanical, thermal, optical, and even chemical characteristics. Model representations of the intrinsic polarity of piezoelectrics are proposed, which are generally described by a third-rank tensor with different spatial distributions of polar directions along which the manifestation of electric polarity is maximal. Polarity was experimentally studied as an electrical response of a crystal to uniform thermal action since, according to the Curie principle, any intrinsic property of a crystal can be convincingly determined only with a scalar (uniform) action on it. As is known, in ten symmetry classes of pyroelectrics, a change in temperature leads to a pyroelectric effect, which allows one to determine their intrinsic polarity, but in the remaining ten symmetry classes of piezoelectrics, the characteristic of their polar-neutral axes compensates for the thermoelectric response. This work demonstrates the possibility of determining the intrinsic polarity in all piezoelectrics with a uniform change in temperature, but under conditions of partial limitation of thermal deformation of the crystal.